Fusarium Crown and Root Rot of Tomato in Florida - Shouan Zhang; Pamela D. Roberts; Geoffrey Meru; Robert J. McGovern; Lawrence E. Datnoff (EDIS)
Update of the 2015 version with Geoffrey Meru includes new integrated management procedures to reduce the impact of crown and root rot.